(untitled) (AmS-Varia, 2016)
Based on the threatening climatic situation confronting the world and the fact that Norway’s geographical position makes the country vulnerable to climate change, this article addresses the paradox that climate has only interested Norwegian istorians to a negligible extent. In a historiographical analysis, a review is made of Norwegian historical research over the last 100 years to establish what place climatic effect and climate change has had on Norwegian historical development. The seeming lack of interest for the subject is contrasted with the opposite international situation and the situation in other relevant subject areas. Characteristically, the degree to which Norwegian historians have been engaged in interdisciplinary cooperation has been small. The starting point has been the firm belief that more knowledge about climate and climate change can contribute significantly to a better understanding of historical development in Norway. It is also argued that, because of this, historians have lost an opportunity to extend the possibilities of coping with the climatic challenges facing society.